USELESS EFFORT EXPRESSIONS IN INDONESIAN PROVERBS - Putu Wijana, I Dewa (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2024)
This research article deals with Indonesian proverbs used to express “useless efforts” with focus of attention on the syntactic structures, and various causal factors that make the works expressed by the verbs impossible to realize. By using data collected from proverb collection book entitled 7700 Perribahasa Indonesia [7700 Indonesian Proverbs], it is found that the Indonesian proverbs convey useless efforts can be delivered through various types of syntactic structure: predicate-object (PO), conjunction-predicate-object (Conj-P-O), predicate-object-adverbial (P-O-Adv), conjunctionpredicate-object-adverbial (Conj-P-O-Adv), predicate-complement (P-Comp), predicate-adverbial (P-Adv), conjunction-predicate-adverbial (Conj-P-Adv), subject-predicate-object (S-P-O), subjectpredicate-adverbial (S-P-Adv), conjunction-predicate-adv (Conj-P-Adv), predicate-subject (P-S), and adverbial-subject-predicate (Adv-S-P). Based on these various types of structure, in the proverbs involving no subject slot, the impossibilities can be caused by the objects, object attributes, complements, and adverbials that explain the location, time, purpose, and instrument by which the efforts are executed. Meanwhile, in the proverbs involving subject constituent, the impossibilities are caused by the subjects filled by words or phrases of having referents human, non human, or entities which are improper or incapable realizing the actions.